2005
DOI: 10.1002/aoc.994
|View full text |Cite
|
Sign up to set email alerts
|

New preparation of gold–silver complexes and optical fibre environmental sensors based on vapochromic [Au2Ag2(C6F5)4(phen)2]n

Abstract: n is isolated as a powder that is able to detect volatile organic compounds such as acetone even in an aqueous solution. The colour of this vapochromic material changes from bright yellow to white in the presence of different donor solvents such as acetone, methanol or ethanol. For the practical construction of an optical fibre sensor, a sol-gel doped with the vapochromic complex was deposited onto one end of a monomode fibre connected to a coupler. The behaviour of the material was studied at different wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 45 publications
(14 reference statements)
1
24
0
Order By: Relevance
“…Recent studies have proven that substitution reactions between the ligand at the Ag atoms and the VOCs are responsible for the observed behaviour, and that the emission is localized in the tetranuclear Au I /Ag I cores [96]. This type of Au I /Ag I polymers can be incorporated into fibre optics for optical measurements [97][98][99][100][101][102]. The coordination polymers {Cu[Au(CN) 2 ](solvent) 2 } n , which can be obtained in two polymorphic forms depending on the solvent, exhibit visible colour changes on exposure to various volatiles, including water, MeCN, DMF, dioxane, pyridine and NH 3 .…”
Section: Detection Of Gases and Volatile Organic Compoundsmentioning
confidence: 98%
“…Recent studies have proven that substitution reactions between the ligand at the Ag atoms and the VOCs are responsible for the observed behaviour, and that the emission is localized in the tetranuclear Au I /Ag I cores [96]. This type of Au I /Ag I polymers can be incorporated into fibre optics for optical measurements [97][98][99][100][101][102]. The coordination polymers {Cu[Au(CN) 2 ](solvent) 2 } n , which can be obtained in two polymorphic forms depending on the solvent, exhibit visible colour changes on exposure to various volatiles, including water, MeCN, DMF, dioxane, pyridine and NH 3 .…”
Section: Detection Of Gases and Volatile Organic Compoundsmentioning
confidence: 98%
“…There is a family of complexes of general formula [AuAg(C 6 F 5 ) 2 L] n , where L is a ligand molecule that can be pyridine, 2,2'bipridine, 1,10 phenantroline, ½ diphenylacetylene and other ligands [10,11], which change from different colour as orange or red to white in the presence of coordinating solvent as acetone, methanol or ethanol. In these cases, the polynuclear structure of starting compound [Au 2 Ag 2 (C 6 F 5 ) 4 (C 6 H 5 N) 2 ] disappears and a new anion-cation derivate is formed as a consequence of the solvent coordination to the silver centre, creaking both the gold-silver bounds and the gold-gold contacts, which are responsible of the initial colour.…”
Section: Iivapocromic Materialsmentioning
confidence: 99%
“…In presence of coordinating solvents as acetone, alcohols or acetic acid, first, the polynuclear structure of the starting complex disappears, getting broken the gold-silver and gold-gold bounds, which are responsible for the initial colour; then, a new anion-cation derivate is formed as a consequence of the solvent coordination to the silver centres (see figure 2), provoking a change in the colour of the complex. Some preliminary fiber optic sensors based on this family of complexes have been already presented and characterized for VOCs detection [17, 18]. …”
Section: Nanosensor Constructionmentioning
confidence: 99%
“…Although the ambient factors sensitivity of the sensor has not been performed in this study, previous results obtained in our group with sensors developed using the ESA technique and the vapochromic material, showed that the response of the device has neither thermal or humidity correlation [17, 18]. Even in more complex sensing schemes and more suitable to be sensitive to temperature than in this case, it is showed that the cross sensitivity to temperature is negligible in the whole spectrum [32].…”
Section: Characteristics Of the Sensormentioning
confidence: 99%
See 1 more Smart Citation